2020
DOI: 10.1002/eat.23243
|View full text |Cite
|
Sign up to set email alerts
|

Association between gastrointestinal complaints and psychopathology in patients with anorexia nervosa

Abstract: Objective: Gastrointestinal (GI) symptoms appear frequently in patients with anorexia nervosa (AN), but the associations between psychopathological, GI, and eating disorder (ED) symptoms remain unclear. This study aimed to determine the relationships of GI complaints with psychopathological measures, ED symptoms, and body mass index (BMI) in patients with AN.Method: Thirty outpatients with AN aged >16 years were included. Psychopathological measures (Symptom Checklist-90-Revised, Beck Depression Inventory-II, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…However, in some cases upper GI symptoms may improve despite no changes in gastric emptying. Hence, it may be that GI visceral hypersensitivity is the underlying abnormality in these patients and increased exposure to visceral sensations during treatment may offer mechanistic explanation of symptom resolution in these cases (Kessler et al, 2020). Further research is needed to disentangle these links.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases upper GI symptoms may improve despite no changes in gastric emptying. Hence, it may be that GI visceral hypersensitivity is the underlying abnormality in these patients and increased exposure to visceral sensations during treatment may offer mechanistic explanation of symptom resolution in these cases (Kessler et al, 2020). Further research is needed to disentangle these links.…”
Section: Discussionmentioning
confidence: 99%
“…Boyd et al (2005) found somatization and anxiety to predict development of individual FGIDs and neuroticism to predict the presence of three or more FGIDs in those with AN. Similarly, Kessler et al (2020) found that the severity of functional GI pain correlated with higher somatization scores in AN. Salvioli et al (2013) found hypochondriasis to predict likelihood of functional GI complaints as well as lack of improvement in symptoms while Ochi et al (2008) found perfectionism traits in AN to correlate with GI symptoms and functional dyspepsia.…”
Section: Resultsmentioning
confidence: 83%
“…Studies suggest a prevalence of FGIDs, prior to ED treatment, ranging from 56 to 97%, depending on the population examined (Boyd et al, 2010; Perez et al, 2013). BMI does not seem to correlate with self‐reported functional GI symptoms prior to weight restoration (Kessler et al, 2020; Perkins et al, 2005; Porcelli et al, 1998; Salvioli et al, 2013), although one study did show that IBS, one of the FGIDs associated with abdominal pain and changes in stool habits, was less prevalent at a normal BMI (defined as 20–25 kg/m 2 ) compared to those whom were underweight; this study did not differentiate individuals suffering from AN, BN, and EDNOS (Abraham & Kellow, 2011). Similarly, Santonicola et al (2012) found a significantly increased frequency of postprandial distress syndrome in underweight patients with AN compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients with eating disorders are about three times more likely than controls to seek treatment for GI problems (Winstead & Willard, 2006). Furthermore, GI problems have been found to be associated with somatization in patients with AN (Kessler et al, 2020). However, the relationship between DGBI and eating disorders is complex and potentially bidirectional.…”
Section: Introductionmentioning
confidence: 99%